(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents methods of how one of the 3 main competences accepted for applied sciences defined in the "National Curriculum" can be used in practice to develop the competence of aesthetic culture and creativity.